Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1002/ana.410170602
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial myopathies

Abstract: Mitochondrial diseases, defined restrictively as disorders due to defects of the mitochondrial respiratory chain, are notoriously heterogeneous, both clinically and genetically. Here, we review only disorders affecting exclusively or predominantly skeletal muscle (mitochondrial myopathies). As the respiratory chain is under dual genetic control, we consider first myopathies due to defects in mitochondrial DNA (mtDNA), distinguishing those due to defects of mitochondrial protein synthesis in toto from those due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
148
1
16

Year Published

1987
1987
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 664 publications
(179 citation statements)
references
References 89 publications
5
148
1
16
Order By: Relevance
“…The present findings further support the role of energy deficiency as an important pathoetiologic agent in Leigh syndrome, as evidenced from reports of the syndrome being caused by defects of the pyruvate dehydrogenase complex (39,40) or cytochrome oxidase (41,42). Moreover, both mtDNA mutations (discussed in this study) as well as nuclear mutations (43) have been demonstrated.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings further support the role of energy deficiency as an important pathoetiologic agent in Leigh syndrome, as evidenced from reports of the syndrome being caused by defects of the pyruvate dehydrogenase complex (39,40) or cytochrome oxidase (41,42). Moreover, both mtDNA mutations (discussed in this study) as well as nuclear mutations (43) have been demonstrated.…”
Section: Discussionsupporting
confidence: 91%
“…Severe intolerance ofphysical exercise associated with elevated blood lactate levels at rest or with minimal exercise is a wellrecognized syndrome of skeletal muscle mitochondrial disease (1,2). In many cases the underlying biochemical abnormality is undefined, but in others a defect involving the respiratory chain in skeletal muscle at the level ofcomplex 1 (NADH-CoQ oxireductase) or complex III (CoQ-cytochrome c oxireductase) has been identified (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe defects in either complex I or cytochrome oxidase had complexe s that were only partially The inb orn errors of metabolism kn own to be primary causes of lacticacidemia include defects in pyru vate carboxylase ( I), th e pyru vate dehydrogenase complex (2), and the respiratory chain (3). Altho ugh the first two produce devastating result s in early life in th ose affected, the majorit y of report ed cases with respiratory chain defects have thus far been older children or adults (4,5). Th ese cases have often been diagnosed after the present ation of " mitoc ho ndrial myopath y" with ab normal mitochondrial appearance in mu scle, either by light or electro n microscop y.…”
mentioning
confidence: 99%